2023
DOI: 10.3390/en16103988
|View full text |Cite
|
Sign up to set email alerts
|

Non-Intrusive Arc Fault Detection and Localization Method Based on the Mann–Kendall Test and Current Decomposition

Abstract: In recent years, electrical fires caused by arc faults have been increasing, seriously affecting the safety of people’s lives and property. Considering the complex arc fault characteristics of actual low-voltage users, the non-intrusive arc fault detection and localization method is studied. First, the characteristics of arc current waveforms are analyzed, and event detection based on the Mann–Kendall Test is performed for the difference between the current waveforms of two adjacent cycles, rather than using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Figure 1 shows the current waveforms at different loads when arc faults occur. Analyzing the waveform characteristics of the arc current, it is found that the current waveforms of different loads after series arc faults contain obvious features such as zero rest, the absence of a semi-period waveform, random fluctuations of the arc current [15][16][17], and high-frequency currents with high amplitudes appearing during the zero rest of inductive load faults [18,19].…”
Section: Arc Signal Feature Extractionmentioning
confidence: 99%
“…Figure 1 shows the current waveforms at different loads when arc faults occur. Analyzing the waveform characteristics of the arc current, it is found that the current waveforms of different loads after series arc faults contain obvious features such as zero rest, the absence of a semi-period waveform, random fluctuations of the arc current [15][16][17], and high-frequency currents with high amplitudes appearing during the zero rest of inductive load faults [18,19].…”
Section: Arc Signal Feature Extractionmentioning
confidence: 99%